A new teiid lizard of the genus Callopistes Gravenhorst, 1838 (Squamata, Teiidae), from the Lower Miocene of Argentina. Issue 4 (4th July 2018) - Quadros, Ana B.; Chafrat, Pablo; Zaher, Hussam
Abstract: Although squamates are commonly found in Cenozoic South American deposits, most findings correspond to fragmentary cranial materials or isolated vertebrae. Among the known South American vertebrate fossil localities, the lower section of the Chichinales Formation (Early Miocene, Colhuehuapian South American Land Mammal Age [SALMA]), in Paso Córdoba Protected Natural Area, Río Negro Province, Argentina, recently yielded an almost complete skull of a previously unknown teiid lizard. Here, we provide a detailed description of this new fossil, based on stereoscopic and high-resolution X-ray computed tomography (CT scan) analyses. Our phylogenetic analysis recovered the new fossil within the monophyletic genus Callopistes, as the sister group of the fossil C. bicuspidatus from upper Miocene–lower Pliocene sediments (Montehermosan SALMA) of the Monte Hermoso Formation. The new species antedates the oldest previously known fossil record of the genus by at least 14 Ma, providing a minimum age of origin for the genus of approximately 20.1 Ma (based on recent revisions of the Cenozoic fossil record of SALMA). The current distribution of the two known extant species of Callopistes and the locality from which the new taxon was recovered indicate that this genus had a much broader distribution in the past that included cis-Andean areas of Patagonia during the Miocene. Our phylogenetic results further suggest that Tupinambis uruguaianensis should be allocated to the genus Dracaena . http://zoobank.org/urn:lsid:zoobank.org:pub:452C7D2A-6819-4488-9C28-1020EBD71F91 SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Quadros, A. B., P. Chafrat, and H. Zaher. 2018. A new teiid lizard of the genus Callopistes Gravenhorst, 1838 (Squamata, Teiidae), from the Lower Miocene of Argentina. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2018.1484754.